Framing a Homeric Hapax: Bacchylides as Homererklärer in the Deianeira/Clytaemestre Connection (B. 16.30) - Skempis, Marios (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2024)
I propound the idea that Bacchylides 16 connects Deianeira with Clytaemestre in four different ways: [1] by means of a Homeric hapax (οἷον ἐμήσατο); [2] by dint of a figura etymologica (μῆτιν/ἐμήσατο); by drawing parallel constructions from a thematic point of view; [4] by exercising Homererklärung through etymologizing in absentia.